Srovnání MRCP a ERCP v diagnostice choledocholitiázy - Vaníček, J; Kyselová, H; Kianička, B; Mikulicová, R; Bajgarová, B; Trna, J; Souček, M; Riháček, I; Spác, J (Vnitrni lekarstvi, 2013)
INTRODUCTION: Choledocholithiasis is the most common cause of biliary obstruction. Each of the testing methods used in its diagnosis has its advantages and disadvantages. OBJECTIVE OF THE STUDY: The objective of this prospective study is to compare endoscopic retrograde cholangiopancreatography with magnetic resonance cholangiopancreatography in the diagnosis of choledocholithiasis on the basis of own experience and literature data. Set of patients and methodology: The set was studied from the beginning of 2007 to the end of 2012 (i.e. six years). The study assessed prospectively 45 patients (age range 28- 72 years) with symptoms of biliary obstruction, who first underwent magnetic resonance cholangiopancreatography and subsequently endoscopic retrograde cholangiopancreatography. RESULTS: The sensitivity, specificity and diagnostic accuracy of magnetic resonance cholangiopancreatography was lower, both in our set of patients and according to the literature data, compared to the endoscopic retrograde cholangiopancreatography (92%, 91% or 93 %). CONCLUSION: Considering the frequency of complications (in some cases serious ones) following endoscopic retrograde cholangiopancreatography, the magnetic resonance cholangiopancreatography is, in spite of its lower sensitivity, the method of choice in the diagnosis of choledocholithiasis by means of noninvasive methods, on the basis of which it is possible to refer the patients subsequently for therapeutic endoscopic retrograde cholangiopancreatography.
Keywords: senioři; Cholangiopancreatography, Magnetic Resonance; senzitivita a specificita; Aged, 80 and over; Middle Aged; Sensitivity and Specificity; magnetická rezonanční cholangiopankreatografie; dospělí; Cholangiopancreatography, Endoscopic Retrograde; senioři nad 80 let; Adult; Humans; Aged; choledocholitiáza; lidé středního věku; lidé; Choledocholithiasis; cholangiopankreatografie endoskopická retrográdní